Thomas Chatterton and Neglected Genius, 1760-1830 - Cook, Daniel. author. aut Link
XV, 259 p.
Keywords: Long before Wordsworth etherealized him as 'the marvellous Boy / The sleepless Soul that perished in its pride', Thomas Chatterton was touted as the 'second Shakespeare' by eighteenth-century Shakespeareans, ranked among the leading British poets by prominent literary critics, and likened to the fashionable modern prose stylists Macpherson, Sterne, and Smollett. His pseudo-medieval Rowley poems, in particular, engendered a renewed fascination with ancient English literature. With Chatterton as its case study, this book offers new insights into the formation and development of literary scholarship in the period, from the periodical press to the public lecture, from the review to the anthology, from textual to biographical criticism. Cook demonstrates that, while major scholars found Chatterton to be a pertinent subject for multiple literary debates in the eighteenth century, by the end of the Romantic period he had become, and still remains, an unsettling model of hubristic genius.